2021
DOI: 10.3390/rs13234844
|View full text |Cite
|
Sign up to set email alerts
|

Sargassum Detection Using Machine Learning Models: A Case Study with the First 6 Months of GOCI-II Imagery

Abstract: A record-breaking agglomeration of Sargassum was packed along the northern Jeju coast in Korea in 2021, and laborers suffered from removing them from the beach. If remote sensing can be used to detect the locations at which Sargassum accumulated in a timely and accurate manner, we could remove them before their arrival and reduce the damage caused by Sargassum. This study aims to detect Sargassum distribution on the coast of Jeju Island using the Geostationary KOMPSAT 2B (GK2B) Geostationary Ocean Color Imager… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Experimental results showed that SRSe-Net is able to obtain more accurate segmentation with fewer network parameters. Shin et al [73] trained three machine learning models with Rayleigh-corrected reflection images and a ground truth map obtained from Geostationary Ocean Color Imager-II (GOCI-II) imagery during the agglomeration of Sargassum along the northern Jeju coast in Korea in 2021, including fine tree, fine Gaussian support vector machine (SVM), and gentle adaptive boosting (Gentle-Boost). Among these, the authors determined that Gentle-Boost was best at detecting the location of Sargassum (Figure 5).…”
Section: Oil Spillsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental results showed that SRSe-Net is able to obtain more accurate segmentation with fewer network parameters. Shin et al [73] trained three machine learning models with Rayleigh-corrected reflection images and a ground truth map obtained from Geostationary Ocean Color Imager-II (GOCI-II) imagery during the agglomeration of Sargassum along the northern Jeju coast in Korea in 2021, including fine tree, fine Gaussian support vector machine (SVM), and gentle adaptive boosting (Gentle-Boost). Among these, the authors determined that Gentle-Boost was best at detecting the location of Sargassum (Figure 5).…”
Section: Oil Spillsmentioning
confidence: 99%
“…In the forecasting of oceanic variables, methodologies broadly fall into two types. The first type of methodology Figure 5: Ground-truth maps and Sargassum maps generated using traditional methods (DVI, SRG, and SI) and machine learning models (fine tree, fine Gaussian SVM, and GentleBoost) from GOCI-II images obtained on 27 January, adapted from Shin et al [73]. Ocean-Land-Atmosphere Research includes traditional numerical models that rely on expert knowledge to develop complex dynamic and thermodynamic equations.…”
Section: Oceanic Phenomena Forecastingmentioning
confidence: 99%
“…Subsequently, South Korea launched GOCI-II in 2020. GOCI-II has many improvements over GOCI, with more watercolor bands and higher spatial resolution [56][57][58].…”
Section: Introductionmentioning
confidence: 99%
“…CEAN color remote sensing data have been widely used for short-and long-term monitoring of water quality [1], [2], [3], [4], ocean productivity [5], ocean fronts [6], and blooms such as red [7], [8], [9], green, and golden tide blooms [10], [11], [12]. Monitoring and assessing water changes are carried out using ocean color sensors such as the Moderate Resolution Imaging Spectroradiometer (MODIS; Terra:1999-present; Aqua:2002-present), Sea-viewing Wide Manuscript received XXX; revised XXX; accepted XXX.…”
Section: Introductionmentioning
confidence: 99%